COMBINATION OF CONCENTRATION PLANT GROWTH REGULATOR ROTOONE-F AND RED ONION FILTRATES TO GROWTH ROSE APPLE SHOOT CUTTING - Fitriani, Rahmidiyani, Ahmad mulyadi, Fitri ani (Jurnal Sains Pertanian Equator, 2019)
The aim of this study was to obtain the best combination of Rotoone-F concentrations and red onion filtrates to growth of shoot cutting rose apple shoot cutting. This research used cansist 7 treatment of growth regulator concetration. The concetration is Concentration used is : without growth regulator ( control); 100% Rotoone-F +0% red onion filtrates; 80% Rotoone-F + 20% red onion filtrates; 60% Rotoone-F + 40% red onion filtrates; 40% Rotoone-F + 60% red onion filtrates; 20% Rotoone-F + 80% red onion filtrates; and 0% Rotoone-F + 100% red onion filtrates. The variables observed are percentage life cutting, number of leaves, number of shoots, length of shoots and number of roots. The results of this study indicate that giving growth regulator substances Rotoone-F with red onion filtrates in various concentrations can improve percentage life cutting and number of roots rose shoot cutting. The concentration of 40% Rotoone-F + 60% red onion filtrates shows the highest of percentage of life cutting and number of roots.Keywords : Red Onion Filtrate, Rose Apple, Rotoone-F, Shoot Cutting